Pengaruh Citra Merek, Price Value, Dan Perceived Usefulness Terhadap Minat Berlangganan Spotify Premium - Abigail Shanen Wulung; Elia Ardyan (Jurnal Online Manajemen ELPEI, 2026)
The accelerating expansion of digital music streaming platforms has prompted firms to better understand the determinants of consumers’ subscription decisions. This study seeks to examine the influence of brand image, price value, and perceived usefulness on users’ intentions to subscribe to Spotify Premium. A quantitative research design was adopted, with data collected through questionnaires administered to Spotify users. The relationships among the variables were analyzed using the Partial Least Squares (PLS) technique. The findings reveal that brand image, price value, and perceived usefulness exert a positive and significant impact on subscription intention. These results indicate that a favorable brand image, a perceived balance between price and benefits, as well as the functional usefulness and convenience of the service are critical drivers in encouraging consumers to subscribe. The study’s implications are expected to offer practical insights for Spotify in formulating more effective marketing strategies, particularly in enhancing brand image, implementing competitive pricing schemes, and continuously improving service quality and features. Furthermore, this research is anticipated to contribute to the broader body of academic literature in marketing and consumer behavior.